2017
DOI: 10.7860/jcdr/2017/24633.9418
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib Induced Cardiac Tamponade- A Rare Association

Abstract: A 48-year-old male patient presented to the cardiology outpatient department with complaints of shortness of breath for the past one month. The onset was insidious and gradually progressive, on ordinary activity to start with and on less than ordinary activity for the past one week. He was diagnosed as a case of CML five years prior to current admission and was on treatment with Imatinib mesylate for three years. However, due to the development of resistance and poor treatment response, he was started on Dasat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…In previous studies, the presence of concomitant heart or lung diseases, hypertension, hypercholesterolemia, autoimmune diseases, skin rash related to treatment, and advanced age were identified as high-risk conditions for the development of effusions (12). Wattal et al reported a case of a CML patient who received 100 mg Dasatinib daily, presented with pleural and pericardial effusion and regressed after Dasatinib treatment interruption (6). In a review of the 13 CML patients treated with 50 or 100 mg Dasatinib, Krauth et al reported that four of the patients developed clinically significant pleural or pericardial effusion, and one of these patients had lifethreatening massive pericardial effusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the presence of concomitant heart or lung diseases, hypertension, hypercholesterolemia, autoimmune diseases, skin rash related to treatment, and advanced age were identified as high-risk conditions for the development of effusions (12). Wattal et al reported a case of a CML patient who received 100 mg Dasatinib daily, presented with pleural and pericardial effusion and regressed after Dasatinib treatment interruption (6). In a review of the 13 CML patients treated with 50 or 100 mg Dasatinib, Krauth et al reported that four of the patients developed clinically significant pleural or pericardial effusion, and one of these patients had lifethreatening massive pericardial effusion.…”
Section: Discussionmentioning
confidence: 99%
“…As the etiology of pericardial effusion is unknown, we considered that there might have been a Dasatinib-associated pericardial effusion after literature research. (6)(7). We directed the patient to hematology, and dasatinib therapy was replaced with Nilotinib again after BCR/ABL gene evaluation.…”
Section: Case Reportmentioning
confidence: 99%
“…On the other hand, pericardial effusion is less reported [11][12][13][14], and mechanisms and management are less established. In a report of 23 patients who received dasatinib, nine patients developed grade I/II pleural effusions, and only one case developed pericardial effusion (grade I/II) [11].…”
Section: Discussionmentioning
confidence: 99%
“…• Ингибиторы протеинкиназы (низкомолекулярные ингибиторы тирозинкиназы: дазатиниб**, иматиниб**) [244];…”
Section: заболевания перикарда связанные с методами лечения ракаunclassified